GRAMATIKALISASI DALAM PETUNJUK PERLATIHAN BUKU TEKS BAHASA INDONESIA SMA KELAS X - Kurniawam, Hindra (Jurnal Pena Indonesia, 2015)
Sentence textbook training manual contains commands that must be understood and carried out as desired student authors.It aims to train students evaluatetheir learning results. Grammatical form changes in the text aims to enable students more easily to reveal a meaning of an instructions contained in a textbook training.Better to understand a changes in grammatically forms, are presented in a textbook process Indonesiangrammatically. In agrammatically process, there will be changes due to become different in meaning,grammatically composition form and structure of a sentence. A meaning can be a new or meaning still retain an old meaning which still survive.A new meaning appear when experiencing a reduction in a sentence element or elements added point. Changes in a core elements as a result of a sentence to change a reader mindset, in predicting a primary purpose of giving guidance n at t on his practice.Meaning that unchanged is a core element of a sentence that remain despite has develop a grammaticallyprocess, so intent submitted n to t remains a same and unchanged. The first discovery process experienced by a guidance desemanticization of his practice due to the loss of semantic elements within a meaning of a word so that experienced more narrow and focused on one speechpurpose.A first discovery process experienced by a guidance lose specific semantic features of human practicing caused by a loss of semantic elements within the meaning of the word so that experienced more narrow and focused on one purpose speech.In an analysis of a sentence mean desemanticization found changes as a result of an analysis partly different and there are mostly suffered ambiguity.Because of an ambiguity can cause t disoriented about what to do with a task that given by n. Desemanticization meaning that changes in affective meaning into thematic, thematic meaning becomes a conceptual, thematic meaning into collocation, and affective be connotative meaning.The meaning of a changes can not be separated from the desemanticization process but that meaning has a value different flavors in each type.